Inter-Village Conflict and Communal Violence in Bima, Indonesia: A Political Sociology Perspective - Jurdi, Syarifuddin; Syarif, Ashila Salsabila; Syarif, Ahmad Mutawakkil (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
This study examines the persistence of inter-village conflict in Bima, West Nusa Tenggara, Indonesia—an ethnically and religiously homogeneous region often regarded as culturally devout. Drawing on a qualitative approach, the research explores how historical memory, youth dynamics, and symbolic narratives contribute to recurring communal violence in a context otherwise associated with Islamic civility. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings reveal that conflict escalation typically follows a three-stage pattern: latent grievances, amplifying factors, and triggering events—often involving youth mobilization around issues of honor, revenge, or misinformation. Economic hardship, unemployment, and low educational attainment among young men further intensify this dynamic. Additionally, institutional responses to early-stage conflicts are often inadequate or absent, enabling escalation and reinforcing cycles of retaliation. While traditional elders play a role in informal mediation, sustainable peace requires a dual-track strategy: early prevention through community engagement, and firm law enforcement when violence erupts. This study offers a localized framework for understanding identity-driven communal violence in ethnically homogeneous rural areas—a domain often overlooked in mainstream conflict literature—and contributes to both the theoretical discourse on horizontal conflict and the practical development of conflict-sensitive governance and youth-oriented peacebuilding.